Peran Imigrasi Kepada Warga Negara Asing dalam Menindaklanjuti Penyalahgunaan Izin Tinggal di Indonesia - Sitanggang, Immanuel Lamhot; Simamora, Janpatar (Innovative: Journal Of Social Science Research, 2025)
The purpose of writing this journal is to understand the role of immigration regarding those who misuse residence permits in Indonesia as a permanent visit location. In this case, it can be understood that such misuse of residence permits is not allowed by the immigration authorities because it can be detrimental to the country. Therefore, the role of immigration includes the task of supervising foreign nationals (WNA) who visit. In this regard, immigration can play an important role by having very strict regulations so that mistakes or disturbances cannot occur in the area. Strict actions can be taken against those who cause disturbances in accordance with the established regulations.